The Tudan's Organic Mulberry Tea: An Indigenous Community Tea Product Made Underutilized Part of Mulberry Plant - Tracy Anak Angki; Fiffy Hanisdah Saikim; Mahadimenakbar Mohamed Dawood; Abdul Hamid Ahmad; Elia Godoong; Azniza Mahyudin; Awangku Hassanal Bahar Pengiran Bagul; Patricia Clementina Matanjun; Nor Qhairul Izzreen Mohd. Noor; Jidon Adrian Janaun; Neoh, Yan Ying; Emmylice Sirinus; et al. (BIMP-EAGA Unit for Tourism Development (BE-UTD), 2018)
Kampung Tudan is located at the rural area and protected under buffer zone of Crocker Range Biosphere Reserve Area by UNESCO, where human and society live in harmony. Mulberry plantations have been introduced as an alternative economic activity to enhance their livelihood. Tudan’s Organic Mulberry Tea was made locally in Kampung Tudan, is an innovative product made up from the mulberry leaves into tea product. Fresh leaves from mulberry plant was harvested, dried using community solar powered dryer for the production of the tea and the formulation is under Trade Secret by the Centre for Research and innovation which belongs to Universiti Malaysia Sabah. A few series of laboratory test have been conducted on Tudan’s Organic Mulberry Tea such as physicochemical analysis and consumer sensory evaluation. Results shows that, mulberry tea powder considerable high in protein with stable shelf life. There were about 100 panels majority from student has been evaluated Tudan’s Organic Mulberry Tea based on four sensory test which are aroma, color, taste, mouthfeel and their overall acceptance. Overall acceptance scores for Tudan’s Organic Mulberry Tea is more than 30%. The newly developed tea product has been undertaken by Kampung Tudan villager’s cooperative, Koperasi Kampung Tudan Berhad and has commercialized in the market since January 2017. The product is priced at RM 19.90 per box and has generated more than RM 95, 081 revenues since January 2017.